E-tourism an innovative approach in marketing and promoting Dinagyang Festival tourism - Amilanto, Marielle Felice L.; Corros, Fritzen Rose C.; Escrupulo, Angelie T.; Fuentes, Camille S.; Lopez, Rizelle Joy F. ([2016].)
Over the past years, there has been increasing focus on the topic of innovation in tourism. This study examines how Information and Communications Technology (ICT), specifically the use of the internet gradually change the tourism industry structure in Iloilo in terms of marketing and promoting the Dinagyang Festival. Important determinants of innovation are akcnowwledged, including the role of Internet, various medium platforms and local nd foreign tourists that will help boost the tourism industry of a certain location. Representation of knowledge is also identified as a critical factor for both the occurrence and nature of innovations. The article consisted of information and details about (1) forms of tourism; (2) research perspectives and frameworks; (3) concept and theories; (4) methodology; and (5) researcher's discussion and recommendations. The findings present the research study's contribution to theoritical discussions, methodological complexity and practical implications in e-tourism as an innovation approach of promoting and marketing Iloilo's Dinagyang events. Based on analysis and content examination, the study reveal that foreign tourists prefer the use of social media as a medium of promoting events while local tourists' initial preference of marketing channel is word of mouth. Word of mouth and Social Media are recognized to be effective marketing channels by the respondents in the study. This exploratory-descriptive research is conducted for the improvement and development of Iloilo's tourism industry based on information collected from several tourism organizations and tourism authorities such as the Iloilo City Tourism and Development Office and the Iloilo Dinagyang Foundation, Inc., and the Target population-Local, Non-local and Foreign Tourists.
Research Paper (Mgt 199-Management Research). -- Iloilo City : University of the Philippines Visayas-College of Management, [2016].